Larval aggregation and competition for food in experimental populations of Chrysomya putoria (Wied.) and Cochliomyia macellaria (F.) (Dipt., Calliphoridae) - Dos Reis, S. F.; Von Zuben, C. J. [UNESP]; Godoy, W. A. C. [UNESP] (Wiley, 1999)
In blowflies, larval aggregation in patches of food can be both intra- and interspecific, depending upon the degree to which competitors are clumped among the patches. In the present study, the implications of spatial aggregation for larval competition was investigated in experimental populations of the introduced blowfly Chrysomya putoria and the native Cochliomyia macellaria, using data from survival to adulthood in a range of single- and double-species larval cultures. The reduction in C. macellaria survival rate in the presence of C. putoria suggests that the former species is the inferior competitor. The results on survival to adulthood for both species in single- and double-species cultures can be explained in the light of the relationship between the level of intra- and interspecific aggregation and the efficiency of the larval feeding process. The possible implications of these results for the population biology of both species in natural environments are discussed.
Keywords: aggregation; food availability; interspecific competition; intraspecific competition; larva; Calliphoridae; Chrysomya putoria; Cochliomyia macellaria; Diptera